The relationship between language learning experience, motivation and some other individual variables of mature foreign language learners - Chłopek, Zofia (Glottodidactica, 2009)
The present paper investigates the issue of motivation of foreign language learners. The main research question, concerning a possible link between the amount of language learning experience and learner motivation, remains unanswered. However, it turns out that a few learner characteristics which some researchers believe to correlate with language learning experience can probably serve as good predictors of foreign language learners’ motivation.